KEPASTIAN HUKUM ARBITRASE PENYELESAIAN SENGKETA BISNIS SESUAI UNDANG-UNDANG NOMOR 30 TAHUN 1999 TENTANG ARBITRASE LEGAL CERTAINTY - Wamnebo, Frangky; TW, Gatut Hendro; Pandiangan, Roni (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The conflict of norms between Article 3 in conjunction with Article 11 of the Arbitration Law and APS with law number 48 of year 2009 the Law Judicial power has resulted in inconsistencies in court decisions The Law Of Torts in the law cases that are boundby arbitration clauses. Decision No.10/Pdt.G/2010/PN.JKT prioritizes Article10 number 48 of year 2009 the Law Judicial power ,while Decision No. 629/PDT/2011/PT. DKI and Decision No. Putusan MA No.862 K/PDT/2013 is guided by the Arbitration Law.The problem formulation used; First, how are the arbitration process arrangements regulated according to Law Number 30 of 1999 concerning Arbitration?Second, what is the legal certainty of implementing arbitration decisions in resolving business disputes? This research aims to analyze the differences in the legal basis used in the three decisions and evaluate legal certainty in resolving regarding unlawful acts the law disputes that are bound by arbitration clauses. The research method used is normative juridical with a statutory, case study, and conceptual approach. The research results show that Article 10 number 48 of year 2009 the Law Judicial power Law is contrary to the principle of pacta sunt servanda and is based on the principle of lex specialis specialiteit,which places the Arbitration Law as a more specific regulation in The Law Of Torts disputes that are bound by arbitration agreements. This conflict of norms creates legal uncertainty, which has the potential to harm the parties. The conclusion research recommends that Article 10 number 48 of year 2009 the Law Judicial power Law be harmonized with the Arbitration Law and encourages judges to make the Arbitration Law the main guideline in The Law Of Torts disputes that are bound by arbitration clauses. This step is important to uphold the principle of pacta sunt servanda and achieve legal certainty